The Effect of Competency and Standard Operating Procedures on Public Satisfaction Through Public Service Quality at The Environmental Service of West Tanjung Jabung Regency - Hidayat, Hilman; Zahari, M.; Hapsara, Osrita (International Journal of Advanced Multidisciplinary, 2026)
Public satisfaction is a crucial indicator in assessing the success of public service delivery. This study aims to analyze the influence of competency and standard operating procedures (SOPs) on public satisfaction, with public service quality as a mediating variable at the Tanjung Jabung Barat Regency Environmental Agency. The research approach used was quantitative, using a survey method. The study population consisted of 390 community users of the Tanjung Jabung Barat Regency Environmental Agency services. Sampling was conducted using the Slovin formula to obtain a representative sample size. Data collection was conducted through questionnaires, which were analyzed using path analysis or Partial Least Squares (PLS). The results indicate that competency and SOPs have a positive and significant effect on public service quality. Furthermore, public service quality has a positive and significant effect on public satisfaction. Competence and SOPs also have an indirect effect on public satisfaction through public service quality. These findings confirm that improving staff competency and consistent SOP implementation can improve service quality, thereby increasing public satisfaction.